Characterization of ethyl acetate and methanol extracts of Commiphora myrrha and evaluating in vitro anti-diabetic and anti-obesity activities - Heba Abdel-Hady, Eman Ahmed El-Wakil, Eman Abdalla Morsi (Journal of Applied Pharmaceutical Science, 2019)
Diabetes mellitus is a clinical disease categorized by hyperglycemia. Reduction of gastrointestinal glucose absorption through the inhibition of carbohydrate digesting enzymes is one of in vitro anti-diabetic therapeutic approach. This investigation aimed to estimate the in vitro anti-diabetic and anti-obesity activities for ethyl acetate and methanol extracts of Commiphora myrrha oleo-gum as well as the identification of the bioactive compounds. Commiphora myrrha was extracted with methanol and ethyl acetate. The two extracts were used to evaluate their α-glucosidase, α-amylase, and pancreatic lipase inhibitory activities. Identification of the bioactive compounds of ethyl acetate was analyzed by GC-MS (gas chromatography-mass spectrometry). The results showed that the ethyl acetate extract had a stronger inhibition activity on α-amylase (IC50 = 54.60 μg/ml) and α-glucosidase (IC50 = 58.7 μg/ml) than methanol extract on α-amylase (IC50 = 124.01 μg/ml) and α-glucosidase (IC50 = 191.2 μg/ml). Also, ethyl acetate extract had a promising inhibitory effect on pancreatic lipase (IC50 = 107.8 μg/ml) than methanol extract (IC50 = 498.1 μg/ml). GC-MS analysis of ethyl acetate extract identified 31 compounds. Among them nobiletin (50.26%), metaproterenol (orciprenaline) (14.99%), morantel (8.86%), and tricetin (3.38%) were the main compounds. These findings proved that C. myrrha has anti-diabetic and anti-obesity inhibition activity may be due to the bioactive compounds with interesting medicinal properties.
Keywords: GC-MS gas chromatograph,α-amylase,α-glucosidase, Pancreatic lipase, flavonoids.